Unsteady aerodynamics of a morphing tandem-wing unmanned aerial vehicle - Zhang, G. Q. (2013)
The effects of unsteady aerodynamics for a tandem-wing unmanned aerial vehicle (UAV) prototype during the morphing stage have been investigated numerically at low Reynolds numbers (Re<10^6). The morphing stage consists of two stages. The ﬁrst stage involves the unfolding of the canards and wings from their initial position in which they were attached and aligned parallel to the UAV fuselage. The second stage involves the rotation of the unfolded canards and wings around the chord axis toward their ﬁnal orientations. Lift and drag coefﬁcients for the canard and wing vary signiﬁcantly, particularly during the second morphing stage. Maximum deviation can be 2 to 14 times higher than the ﬁnal steady state values. A signiﬁcant increase in the hinge moment is also observed during the ﬁrst morphing stage but the sign of the moment remains the same throughout. The unsteady aerodynamics, however, have larger effects during the second morphing stage, including the rapid change in the sign for the hinge moment, the corresponding magnitude also differs by (+) 57% and (+) 260% for the canard and wing, respectively. Attempts have been made to correlate these observations with the vortex interactions between the canard and wing during the morphing process.